Functionalization and patterning of nanocellulose films by surface-bound nanoparticles of hydrolyzable tannins and multivalent metal ions. Issue 41 (17th July 2019) - Limaye, Mukta V.; Schütz, Christina; Kriechbaum, Konstantin; Wohlert, Jakob; Bacsik, Zoltán; Wohlert, Malin; Xia, Wei; Pléa, Mama; Dembele, Cheick; Salazar-Alvarez, German; Bergström, Lennart
Abstract : Functionalization and patterning of nanocellulose with tannin–metal ion complexes. Abstract : Inspired by the Bogolanfini dyeing technique, we report how flexible nanofibrillated cellulose (CNF) films can be functionalized and patterned by surface-bound nanoparticles of hydrolyzable tannins and multivalent metal ions with tunable colors. Molecular dynamics simulations show that gallic acid (GA) and ellagic acid (EA) rapidly adsorb and assemble on the CNF surface, and atomic force microscopy confirms that nanosized GA assemblies cover the surface of the CNF. CNF films were patterned with tannin–metal ion nanoparticles by an in-fibre reaction between the pre-impregnated tannin and the metal ions in the printing ink. Spectroscopic studies show that the Fe III/II ions interact with GA and form surface-bound, stable GA–Fe III/II nanoparticles. The functionalization and patterning of CNF films with metal ion–hydrolyzable tannin nanoparticles is a versatile route to functionalize films based on renewable materials and of interest for biomedical and environmental applications.